DEVELOPMENT OF "CREATIVE THINKING" SKILLS IN THE TEACHING OF THE STRUCTURE OF PLANTS IN THE 1ST GRADE - Murodova Aziza Sobirjonovna (Journals Park Publishing, 2024)
Creative thinking is a cornerstone of modern education, enabling young learners to approach challenges with innovation and adaptability. Teaching the structure of plants to first-grade students offers an opportunity to nurture these skills through inquiry-based, hands-on, and imaginative activities. This paper explores strategies for developing creative thinking in young learners while teaching plant anatomy, such as roots, stems, leaves, and flowers. The study also identifies challenges in fostering creativity in early education and presents evidence-based methods to overcome them. By examining existing literature and integrating classroom practices, this research highlights the importance of creativity in understanding scientific concepts and developing lifelong problem-solving abilities.
Keywords: Creative thinking, plant structure, 1st grade education, inquiry-based learning, hands-on activities, early childhood education, creativity in science education.